Issues encountered in the application of multiaxial fatigue strength methods to experiments with various stress distributions. (August 2021) - Fojtík, František; Papuga, Jan
Highlights: A unique method combining size and stress distribution effects is developed. It is assessed on 34 different multiaxial load cases with various specimen designs. Seven multiaxial fatigue strength methods are assessed. PCRN method reaches the best output, the MMP method is only slightly worse. The McDiarmid criterion provides good output despite its two-parametric character. Abstract: This paper attempts to describe the effect of a non-constant stress distribution on the fatigue strength of unnotched hollow specimens of various sizes and loaded by different load combinations. The chosen solution evaluates the critical volume, which decides the level of fatigue damage. It relates dimensions of these critical entities to component fatigue strengths, which replace the material parameters in multiaxial fatigue strength criteria. The output shows that the proposed critical volume method is a promising solution. The PCRN and MMP multiaxial fatigue strength methods result in the best prediction outputs from the seven methods assessed here.